Decay widths of Isoscalar Giant Monopole Resonances: regular and chaotic dynamics - Papachristou, P. K.; Mavrommatis, E.; Constantoudis, V.; Diakonos, F. K.; Wambach, J. (HNPS Advances in Nuclear Physics, 2020)
The decay of the Isoscalar Giant Monopole Resonances (IGMR) in the nuclei 208Pb, 144Sm, 116Sn and 90Zr is studied by means of a classical model consisting of several noninteracting nucleons moving in a potential well with an oscillating wall (nuclear surface). The motion of the nuclear surface is described by means of a collective variable which appears explicitly in the Hamiltonian as an additional degree of freedom. The total energy of the system is therefore conserved. Although the particles do not directly interact with each other, their motions are indirectly coupled by means of their interaction with the moving nuclear surface. Despite its simplicity and its purely classical nature, the model reproduces the trend of the experimental data which show that with increasing mass number the decay width decreases. Moreover, with the proper choice of the free parameters, the calculated decay widths are in good agreement with the experimental results. It seems that this agreement is dictated by the corresponding behaviour of the maximum Lyapunov exponent as a function of the system size.